Attitudes of Decision Makers on the Role of Information Technology in Business Decisions - Skyrius, Rimvydas (Ekonomika, 2003)
The history and experience in the field of computerized decision support shows that the field has been evolving from simple fulfilment of decision information needs to intelligent systems and decision automation, and from there to human-centered systems, where the role of IT is two-sided: it has to be natural and unintrusive part of the user’s environment, and at the same time be powerful enough to provide flexible and efficient decision support. This approach requires a substantial knowledge of the user behaviour and environment, shifting the research emphasis from technology functions to user features, activity habits and structures, experiences and beliefs. The goal of this work is to evaluate the current potential of ITbased decision support through the attitudes of the decision makers themselves, combined with the existing research in the field. The article is based on the interviews with business decision makers rom different areas, performed in 1999–2002.